Microencapsulation of green tea extracts: its incorporation into and effects on the physico-chemical and functional properties of mango drinks - Alkali, Zokti James; Baharin, Badlishah Sham; Mohammed, Abdulkarim Sabo; Abas, Faridah (IJENS Publishers, 2016)
Green tea polyphenols have been reported to possess many biological properties. Inspite of the many potential benefits of green tea extracts, their sensitivity to high temperature, pH and oxygen is a major disadvantage towards its effective utilization in the food industry. Green tea leaves from Cameron highlands Malaysia were extracted using SFE. To improve the stability, the green tea extracts was encapsulated by spray-drying using different carrier materials including maltodextrin (MD), gum arabic (GA) and chitosan (CTS) and their combination at different ratios. Encapsulation efficiency, total phenolic content and antioxidant capacity were determined and were found to be in the range of 71.41 - 88.04%, 19.32 - 24.90 (g100GAE), and 29. 52 -38.05% respectively. Further analysis of moisture content, water activity, hygroscopicity and bulk density of the microparticles were carried out and the results ranged from; 2.31 – 5.11%, 0.28 – 0.36, 3.22 – 4.71% and 0.22 – 0.28g/cm3, respectively. The ability of the microparticles to swell in SGF and SIF was determined at 142.00 -188.63% and 207.55 -231.77% respectively. The microparticles with the best catechin efficiency, total phenolic content and antioxidant activity were selected and incorporated into mango drink and its effects on the physicochemical and functional properties of the product evaluated during storage. The pH, total solid and viscosity of the catechin microparticles supplemented range from 5.15 – 4.38, 12.70 – 14.20%, and 12.55 -13.99(cps) respectively. The stability of green tea bioactives in the mango drink showed degradation rate in the range of 16.47 – 29.72% compared to the non-encapsulated powder (46.46%). The green tea extracts microparticles show good degree of stability in the mango drink and the antioxidant capacity of the mango drink was significantly ( p ≥ 0.05) different compared to the non-encapsulated powder at the end of the storage period.